The 48 XXYY Syndrome in a Beninese Child: Clinical Features and Genetic Considerations - AZONBAKIN, Simon; ADJAGBA MARIUS, MARIUS; NBOUKE, Natacha; ADOVOEKPE, Diane; AGBALINSOU, Arnaud; ALAO, MODJÉRÉ OLA MAROUFOU JULES; Gangbo, Flore; LALEYE, OLABISSI ANATOLE A. (My University, 2018)
Abstract The 48 XXYY syndrome is a distinct clinical and genetic entity with an incidence of 1/40000 to 1/18000. A 15-month-old child was admitted in genetic clinics for psycho-motor delayed management. The patient disclosed a dysmorphism with hypertelorism, up slanting palpebral fissure, broad, high and bulging forehead, hypertelorism, very marked furrow of the filtrum and the mouth in the shape of a cocked hat, a microstomy and a development delay. The Karyotype study showed a 48, XXYY chromosome which was present in all analyzed cells. Here, we report a case of a patient with 48, XXYY syndrome diagnosed at the age of 15 months old in order to show the particularities of this syndrome in a beninese child.
Keywords: 48 XXYY syndrome; Development delay; Dysmorphism